Maternal Care-Providing Cichlid Neolamprologus furcifer Selectively Focuses on High-Threat Carnivorous Intruders, Limiting Attention to Other Threats - Satoh, Shun; Hotta, Takashi; Kohda, Masanori (Frontiers in Ecology and Evolution, 2021)
Animals adjust their behaviors based on information from multiple sources; however, the brain can effectively process limited amounts of information. Therefore, attention is restricted to a small portion of environmental stimuli. When animals process multiple information inputs, focusing on information that is deemed important improves detection probability. However, selective focus limits attention to other stimuli and associated behavioral responses. In this study, we examined how Tanganyikan cichlid, Neolamprologus furcifer, mothers selectively attack intruder fishes depending on the threat level and presence or absence of offspring. Species composition is complicated in Lake Tanganyika, and fish density is exceedingly high. Thus, parents must focus on high-threat-level intruders according to their parental care stage. Compared to females without offspring, mothers preferentially attacked carnivorous fishes farther from the nest over closer scale-eating fishes. Moreover, the percentage of females with injuries from scale-eating fish was significantly higher in those caring for offspring than those without offspring, demonstrating the cost of limited attention. Our results show that females focus on the early detection of carnivorous fishes because these predators dart in from long distances to forage eggs, fry and juveniles, but this selective focus limits the attention placed on low-level threats. This study is the first to document the cost of limited attention in parents guarding offspring.